Ultrafast sub-30-fs all-optical switching based on gallium phosphide - Grinblat, Gustavo Sergio (2019)
Gallium phosphide (GaP) is one of the few available materials with strong optical nonlinearity and negligible losses in the visible (l > 450 nm) and near-infrared regime. In this work, we demonstrate that a GaP film can generate sub–30-fs (full width at half maximum) transmission modulation of up to ~70% in the 600- to 1000-nm wavelength range. Nonlinear simulations using parameters measured by the Z-scan approach indicate that the transmission modulation arises from the optical Kerr effect and two-photon absorption. Because of the absence of linear absorption, no slower free-carrier contribution is detected. These findings place GaP as a promising ultrafast material for all-optical switching at modulation speeds of up to 20 THz.